Biosensors Perancangan dan Pengembangan Biosensor untuk Deteksi Kualitas Perairan Laut Berbasis Piranti Mikrokontroler ESP32: Perancangan dan Pengembangan Biosensor untuk Deteksi Kualitas Perairan Laut Berbasis Piranti Mikrokontroler ESP32 - Maman Rumanta; Rony Marsyal Kunda; Fredrik Manuhutu (Postgraduate, University of Mataram, 2024)
Water quality in cultivating marine organisms is a very important part to pay attention to. Prevention of pollution in marine waters needs to be done by recognizing changes in physical, chemical and biological parameters in these waters from normal conditions. To find out these changes, it is necessary to carry out measurements which include parameters that determine the quality of a liquid and carry them out periodically. The measurement parameters measured include pH, Dissolved Oxygen (DO), Electrical Conductivity (EC) and temperature. The use of technological developments, especially in the world of microcontrollers, namely the ESP32 device, makes it possible to design measurement instruments in determining the quality of sea waters to be more efficient and comprehensive. The instrument created in this research will be equipped with several sensors that will read the parameters that determine water quality. The sensors used are pH sensors, DO sensors, EC sensors and temperature sensors. This research aims to create an integrated instrument (pH, DO, ED and Temperature) with instrument performance specifications that have good accuracy and a portable design so that it is easy to use in the field. The research results show thatdevelopment of a biosensor instrument for measuring seawater quality based on the ESP32 DevKit V1 can work well and can display temperature, degree of acidity (pH), DO and EC parameters on the LCD screen according to actual conditions with a difference range in percent between 0.2% - 4.16 %. The accuracy level of the designed tool is classified as having a high accuracy above 95%